2008
DOI: 10.1111/j.1750-3841.2008.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Dried Plum Ingredients in Raw and Precooked Pork Sausage

Abstract: Raw pork sausages with no antioxidant (control), 3% or 6% dried plum puree (DP), 3% or 6% dried plum and apple puree (DPA), or 0.02% butylated hydroxytoluene and butylated hydroxyanisole (BHA/BHT) were (1) stored raw in chubs at 4 degrees C (RR) and evaluated weekly over 28 d, (2) cooked as patties, vacuum packaged, and stored at 4 degrees C (PR) for weekly evaluation over 28 d, or (3) cooked, vacuum packaged, and stored at -20 degrees C (PF) and evaluated monthly over 90 d. DP at 3% or 6% levels was as effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Currently, there is a lack of useful data regarding the presence of AJNE in sausages, but lipid oxidation reduction could be attributed to the presence of polyphenols, rich in anthocyanins (Yoshida et al, 1999; Han et al, 2005) as well as other saponins, inokosterone, ecdysterone and eleanoic acid bisdesmoside (Hahn and Lee, 1991; Ida et al, 1994) in plant extracts. The finding of the present report is in agreement with the findings of the several other studies, which have reported, the successful inhibition of lipid oxidation in many processed meat products using natural antioxidants of plant origin (Formanek et al, 2003; O'Grady et al, 2008; Nunez de Gonzalez et al, 2008; Devatkal et al, 2010). Another explanation for decrease in POV values in AJNE added-sausages is also possible.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, there is a lack of useful data regarding the presence of AJNE in sausages, but lipid oxidation reduction could be attributed to the presence of polyphenols, rich in anthocyanins (Yoshida et al, 1999; Han et al, 2005) as well as other saponins, inokosterone, ecdysterone and eleanoic acid bisdesmoside (Hahn and Lee, 1991; Ida et al, 1994) in plant extracts. The finding of the present report is in agreement with the findings of the several other studies, which have reported, the successful inhibition of lipid oxidation in many processed meat products using natural antioxidants of plant origin (Formanek et al, 2003; O'Grady et al, 2008; Nunez de Gonzalez et al, 2008; Devatkal et al, 2010). Another explanation for decrease in POV values in AJNE added-sausages is also possible.…”
Section: Discussionsupporting
confidence: 93%
“…Positive results were reported for cooked sausages, 106 ham, 107 roast beef, 108 lean beef cuts 109 and turkey breast. 110 Evidence on the stability of the antioxidant capacity during storage was also recorded; 106 however, the processed plum produced negative effects on color, 107,110 and higher cooking loss and shear strength. 107 Cranberry has been widely studied because of its high levels of anthocyanins, which are phenolic compounds with a strong ability to inhibit lipid oxidation.…”
Section: Antioxidant Compounds Derived From Fruit Processingmentioning
confidence: 70%
“…Cáceres et al (2006) reported that the addition of calcium salts (calcium lactate, calcium gluconate, and calcium citrate) caused the hardening of sausages, compared to products not treated with additives. Generally, hardness was highly correlated with moisture content of meat products, where the higher moisture contents the more tender (Casco et al , 2013; Nuñez de Gonzalez et al , 2008). As previously described, the moisture content in this study was similar between the control and the samples treated with ESC, OSC, or MAC.…”
Section: Resultsmentioning
confidence: 99%